Pretending to Understand Among Japanese Language Learners: An Investigation of Occurrence Contexts and Associated Emotions - Kirstie Sobue (CV. Rustam, 2025)
The fact that second language learners commonly employ “pretending to understand” as a communication strategy should be evident to anyone with experience living in a foreign language environment or involved in foreign language education. This study investigates the experiences of pretending to understand among international undergraduate students enrolled at Japanese universities. Using text mining methodology with KH Coder software, this research clarifies in what situations pretending to understand is likely to occur and what emotions are experienced when engaging in this behavior. The survey was conducted from late 2020 to spring 2023 with 142 international undergraduate students averaging N3-N2 Japanese language proficiency level. In contrast to attaining a sense of being part of the group or feeling of achievement, as suggested in prior research, a majority of international students are shown to experience guilty feelings and negative emotions when pretending to understand. Analysis revealed that 43.4% of nouns, 81.3% of adjectival nouns, and up to 86.3% of adjectives used in responses expressed negative emotions. Given that prior research indicates negative emotions may impede learning, this study proposes that Japanese language educators develop further understanding of the phenomenon of pretending to understand, which can lead to loss of confidence and self-reproach among learners.